Consent in Data Privacy: A General Comparison of GDPR and HIPAA - Jurczuk, Magdalena; Suprunowicz, Maria (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2024)
The purpose of this paper is to conduct a general comparisonof legal requirements regarding consent under the Health Insurance Portability and Accountability Act (HIPAA) and the General Data Protection Regulation (GDPR). Both regulations aim to protect health data as a special category of personal data, highlighting the importance of obtaining explicitconsent or authorization from the data owner before processing or disclosing the information. The article explores the distinct approaches of HIPAA and the GDPR in defining consent and authorization, the requirements for withdrawal or revocation of consent, and the form and language of consent. It also examines the scope of application and the impact on healthcare operations, emphasizing the need for informed and transparent consent practices under both regulations. Furthermore, it examines the differences in the regulatory scopes and the specific measures each framework takes to safeguard personal health information.